Legal Issues and Challenges in Regulating the Rights to Wayleave in Malaysia - Sarah Sulaiman, Siti; Md Khali, Rasyikah; Hamizah Aminudin, Nur (International Journal of Engineering and Technology, 2018)
Electricity flows through power lines and other transmission infrastructure to houses, hospitals, offices and other customers’ premises. Due to rapid development and industrialization as well as urbanisation, the demand for energy supply had increased in Malaysia. Thus the electricity supply system need to be strengthen in order to avoid frequent tripping and to provide sufficient, quality and reliable system. There are several ways to improve the electricity supply system namely by building higher volt transmission tower and building more substation and power stations. This paper legally analyse the issues faced by the Tenaga Nasional Berhad (TNB), the main electricity supplier in Malaysia in meeting the increasing demand of electricity while at the same time ensuring public rights are protected. In particular, this paper addresses the issues in regulating the rights to wayleave for electricity supply lines. Towards this ends, relevant laws and case studies are presented to provide a bigger perspective on how the rights to wayleave can affect the other basic human rights.